The peculiar dust shell of Nova DZ Cru (2003) - Evans, Aneurin; Gehrz, R. D.; Woodward, C. E.; Helton, L. A.; Rushton, M. T.; Bode, M. F.; Krautter, Joachim; Lyke, J.; Lynch, D. K.; Ness, J.-U.; Starrfield, S.; Truran, J. W.; et al. (Monthly notices of the Royal Astronomical Society. Letters, 2010)
We present Spitzer Space Telescope observations of the ‘peculiar variable’ DZ Cru, identified by Rushton et al. as a classical nova. A dust shell, on which are superimposed a number of features, is prominent in the 5-35μm range some 4 yr after eruption. We suggest that the dust in DZ Cru is primarily hydrogenated amorphous carbon in which aliphatic bands currently predominate and which may become either predominantly aromatic as the dust is photoprocessed by ultraviolet radiation from the stellar remnant or more likely completely destroyed.